Ogallala, Third Edition : Water for a Dry Land - Opie, John, 1934-; Archer, Kenna Lang, 1982-; Miller, Char, 1951- (Book collections on Project MUSE., 2018)
"The Ogallala aquifer, a vast underground water reserve extending from South Dakota through Texas, is the product of eons of accumulated glacial melts, ancient Rocky Mountain snowmelts, and rainfall, all percolating slowly through gravel beds hundreds of feet thick. Ogallala: Water for a Dry Land is an environmental history and historical geography that tells the story of human defiance and human commitment within the Ogallala region. It describes the Great Plains' natural resources, the history of settlement and dryland farming, and the remarkable irrigation technologies that have industrialized farming in the region. This newly updated third edition discusses three main issues: long-term drought and its implications, the efforts of several key groundwater management districts to regulate the aquifer, and T. Boone Pickens's failed effort to capture water from the aquifer to supply major Texas urban areas. This edition also describes the fierce independence of Texas ranchers and farmers who reject any governmental or bureaucratic intervention in their use of water, and it updates information about the impact of climate change on the aquifer and agriculture."